Drivers of Financial Performance in Islamic Commercial Banks: The Role of GCG Mechanisms and Firm Size - Muhammad Imam Syafei; Emi Yulia Siska; Muhammadinah (Journal of Applied Management and Business, 2026)
Aims - This study aims to analyze the influence of internal Good Corporate Governance (GCG) mechanisms and firm size on the financial performance of Islamic Commercial Banks (Bank Umum Syariah) for the 2020–2024 period. Methodology - A quantitative approach was employed using secondary data from annual reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK). Internal GCG is proxied by institutional and managerial ownership, while financial performance is measured by Return on Equity (ROE). Data were analysed using multiple linear regression with Eviews 13 software. Findings - The regression results indicate that internal GCG has a positive and significant effect on ROE (β = 0.6209; p < 0.000), while firm size also shows a significant positive effect (β = 0.0837; p < 0.000). The overall model is statistically significant (F = 72.30; p < 0.000) with a strong explanatory power (Adjusted R² = 0.9412), suggesting that GCG mechanisms and firm size are key drivers of financial performance in Islamic commercial banks. Research Limitations - The study is limited to internal governance proxies and a specific time frame, future research could incorporate external governance variables or macroeconomic factors. Practically, this study encourages Islamic banks to optimize their ownership structures to strengthen financial stability. Originality - This research provides updated empirical evidence on the resilience of Islamic banking performance during the 2020–2024 period, highlighting how internal governance serves as a strategic pillar amidst evolving economic challenges.